CORRELATION BETWEEN STEM DIAMETER AND PLANT HEIGHT CUT OF TO THE PRODUCTION OF Gliricidia sepium ”PROVENANCE” RETALHULEU WHICH PLANTED IN DRY LAND BUKIT PECATU - Billawa, Dean; Puger, A. W.; Suranjaya, I G. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
The research was conducted to aim the correlation between stem diameter and height cut off plant to the production of Gliricidia sepium “provenance” Retalhuleu used alley cropping which planted in dry land. Research was conducted in Dusun Belawah Sari, Pecatu Village, South Kuta District, Badung Regency during the 6 months of the research. The research method used sample purposive random sampling survey method. The observed variables are plant height, stem diameter, number of branches, number of leaves, dry weight of branch, and dry weight of leaf. The data obtained were analyzed by description and correlation and multiple linear regression. The results showed that there was a significant multiple linear relationship between gamal (y) production with stem diameter (x 1 ) and cut off plant height (x 2 ). The production of forage gamal "provenance" Retalhuleu is positively correlated and low coefficient of determination (R 2 ) value to forage production. Based on the research results can be concluded there is a positive or significantly relationship between stem diameter and height of plant on the production of forage Gliricidia sepium and but low contribution between stem diameter and height of plant to forage gamal production are low. Key words: stem diameter, Gliricidia sepium , height of cutting